ADSORPTION OF FLUORENE USING MOLECULARY IMPRINTED POLYMER (MIP) - Rahadian Nur Jabbar R, Muhammad
Polycyclic Aromatic Hydrocarbons (PAH) is a persistent organic pollutant compounds (POPs) It dispersed through air, water, and settles on the river surface. These compounds can be removed by various methods, one of which is adsorption because PAHs have low solubility in water and have high adsorption in solid media. Fluorene is a type of PAH with low molecular weight (LMW) and toxic in wáter environment. Molecular imprinted polymers can be an alternative for organic pollutant adsorption because they have advantages, such as high selectivity, high stability and low cost to apply to target molecules. Polymers are made using functional monomers, crosslinkers and template molecules. Functional monomers and template molecules are bonded by non-covalent interactions, such as hydrogen bonds and van der Waals forces. This study aims to synthesize, characterize and evaluate the adsorption performance of fluorene-based imprinted polymers. This study examines adsorption kinetic, thermodynamic, isotherm models and their selectivity for other types of LMW PAHs. The imprinted polymer was synthesized using fluorene as a template molecule, divinyl benzene as a functional monomer and ethylene glycol dimethacrylate as a crosslinker with a mole composition of 1:4:20 in acetonitrile using the bulk method. Characterization by FTIR spectra showed several peaks at wave number 3440 cm-1 in the form of hydroxyl (O-H), 2965 cm-1 in the form of alkanes (C-H), 1735 cm-1 in the form of carbonyl (C=O) and 1464-1148 cm-1 aromatic (C=C). SEM characterization can showes difference from NIP, MIP and MIP leached at 2,500x and 20,000x magnification. NIP showed poor results, but MIP and MIP leached results showed uniform surface results with a spherical shape and microsphere size, which is around 3.51 ?m. The adsorption performance of the imprinted polymer showed optimal results at a contact time of 15 minutes, a mass of adsorbent of 20 mg, an initial concentration of 1.2 ppm and an increase in adsorption capacity at temperatures of 25, 40 and 60 oC. Studies of fluorene adsorption showed that non-imprinted polymer (NIP) and molecularly imprinted polymer (MIP) belong to pseudo-second-order reaction kinetics, with an MIP adsorption capacity of 15.19 mg/g and 11.11 mg/g for NIP. The adsorption thermodynamics shows that the reaction is exothermic, runs spontaneously and the adsorption isotherm follows the Langmuir isotherm model. The selectivity of the MIP adsorbent has been tested using a similar PAH, namely phenanthrene, with an ? (selectivity factor) value of 1.13 indicating that MIP is selective for fluorene.